Cluster analysis of bread wheat genotypes for quality traits and yield under late sown conditions at Kymorehills of Narmada Valley - Singh, Monika; Jat, Vinod; Shukla, Rama Shankar; Prasad, Sakuru Venkata Sai (Journal of Cereal Research, 2025)
High temperature stress during late planting conditions specifically at the time of grain filling adversely affects the quality of grain by reducing plant growth and ultimately the nutrient content of sink that is grain. Quality traits such as sedimentation value (mm), protein %, starch %, wet gluten, moisture content and grain yield plant-1, were studied in thirty bread wheat genotypes with three replications in randomized block design, seed breeding farm, J.N.K.V.V., Jabalpur, during the year 2012 and 2013 with the target to cluster genotypes with superior quality in response to heat stress during late planting. A Dendrogram was obtained that is based on variance dividing the total genotypes in seven clusters with distinct characteristics, and grouped under two major clusters A and B. Cluster I to IV belong to group A whereas cluster B had V and VI cluster. Cluster I had maximum and cluster VII had minimum genotypes. Cluster VII and cluster IV showed maximum inter cluster distance and intra cluster distance were maximum in cluster VII. Further, Cluster VII consist of genotypes with maximum sedimentation value (35.500), cluster I had genotypes with maximum hectoliter weight, cluster VII had genotypes with highest protein %, cluster IV had maximum wet gluten, cluster V had genotypes with maximum starch content, maximum moisture level after harvesting was observed in genotypes under cluster IV, whereas genotypes with maximum grain yield fall under cluster IV, were found most tolerant to terminal heat stress. The genotypes MP-3368/MP-4669 and 31ESWYT-123 are highest yielding genotypes belonging to superior cluster IV and considered as very important for developing heat tolerant variety with good quality index and other plant breeding strategies. Keywords: Bread wheat, Dendrogram, Inter-cluster distance, Intra-cluster distance, Heat stress